Sugar Contents of Juniper Plants - TURKOGLU, NALAN; FIKRET BALTA, MEHMET; CIG, ARZU (Asian Journal of Chemistry, 2010)
The contents of free sugar has been confirmed inside the fresh foliage and berry samples gathered from the tree types which are naturally growing in different locations of the province Van and from the tall juniper which is one of the types of Turkish frost trees. It is determined that the average fructose content inside the fresh needle foliage is 44.0-70.2 mg/100 g, average sucrose is 10.0-25.0 mg/100 g, average glucose 22.0-26.0 mg/100 g and average di-glucose (maltoz) content is 5.0-17.0 mg/100 g. It has been found that the free sugar content of berry is higher than the sugar content of foliage, except di-glucose.